Manejo integrado de la corchosis en Veracruz, México - Castillo Ponce, G.
Sumario (Es)
Ilus.
Keywords: COFFEA; MELOIDOGYNE INCOGNITA; PRATYLENCHUS; FUSARIUM OXYSPORUM; TRICHODERMA; CONTROL DE NEMATODOS; MEXICO